KARAKTER MANUSIA DALAM KISAH-KISAH AL-QUR’AN - Ahmad Farhan (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2016)
The Qur'an is the holy book that governs all aspects of human life. As a book, the Qur’an has strength throughout human history. As an ocean of knowledge, the Qur’an would have dived, explored, studied and explored its values. To get the message of this divine message properly, the Qur'an using methods revolves known as Qas}}as} al-Qur'an. The story of the preaching of the Qur’an about the happenings the people of the past, prophetic earlier and the events that have occurred. In addition, the stories of the Qur'an also also contains descriptions of the events of the past, the history of nations, state lands and relics or traces of any race. One lesson that can be drawn is how the Qur’an is about the life of the Prophet whose character is reflected in the stories presented illustrations. Moses, Abraham and Joseph, who had a different character that can take the lesson. Here are, we can see how the Qur’an so beautifully depicts the three characters in the story to be a lesson for humans.